2014
DOI: 10.2139/ssrn.2504541
|View full text |Cite
|
Sign up to set email alerts
|

Peer Effects and Risk Sharing in Experimental Asset Markets

Abstract: Previous research has documented strong peer effects in risk taking, but little is known about how such social influences affect market outcomes. The consequences of social interactions are hard to isolate in financial data, and theoretically it is not clear whether peer effects should increase or decrease risk sharing. We design an experimental asset market with multiple risky assets and study how exogenous variation in real-time information about the portfolios of peer group members affects aggregate and ind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 50 publications
0
5
0
Order By: Relevance
“…In order to improve the selection of experts, researchers proposed an algorithmic system that helps to identify and visualize expert traders based on their performance, risk, and consistency history (Lee and Ma, 2015). Furthermore, platform enabled social cues on individual (i.e., detailed decision information from peers) and network levels (i.e., aggregated decisions from the crowd) have been found to improve the risk management of otherwise risk averse investors (Zhao et al, 2015) by reducing under-diversification (Baghestanian et al, 2015). This effect, however, partially depends on the way in which the related peer information is framed.…”
Section: Remuneration and Incentive Schemesmentioning
confidence: 99%
See 1 more Smart Citation
“…In order to improve the selection of experts, researchers proposed an algorithmic system that helps to identify and visualize expert traders based on their performance, risk, and consistency history (Lee and Ma, 2015). Furthermore, platform enabled social cues on individual (i.e., detailed decision information from peers) and network levels (i.e., aggregated decisions from the crowd) have been found to improve the risk management of otherwise risk averse investors (Zhao et al, 2015) by reducing under-diversification (Baghestanian et al, 2015). This effect, however, partially depends on the way in which the related peer information is framed.…”
Section: Remuneration and Incentive Schemesmentioning
confidence: 99%
“…This effect, however, partially depends on the way in which the related peer information is framed. Prominently displaying the highest earning trader can actually increase the risk affinity of the other users (Baghestanian et al, 2015). This is particularly relevant, since especially traders with a good past performance publicly present their strategies (Amman and Schaub, 2016), which might move people to underestimate risks.…”
Section: Remuneration and Incentive Schemesmentioning
confidence: 99%
“…Upward performance comparison (Schoenberg & Haruvy, 2012) and larger wealth inequality among market players (Deck, Hao, Xu & Yeager, 2021) lead to higher market prices and bubble metrics. Conversely, Baghestanian, Gortner and van der Weele (2015) found that exposing participants to the worst player's performance leads to less risky portfolio allocations.…”
Section: Upward Social Comparison In Financementioning
confidence: 96%
“…Baghestanian et al (2014) examined the moderating effect of characteristic variables . In their study, participants were aware of the portfolio choices of others.…”
Section: Prior Research and Future Research Opportunitiesmentioning
confidence: 99%
“…Additionally, prices remain greater than the fundamental value for a longer period. Baghestanian et al (2014) examined the moderating effect of characteristic variables. In their study, participants were aware of the portfolio choices of others.…”
Section: 6mentioning
confidence: 99%